2015
DOI: 10.1051/0004-6361/201424798
|View full text |Cite
|
Sign up to set email alerts
|

Substellar fragmentation in self-gravitating fluids with a major phase transition

Abstract: Context. The observation of various ices in cold molecular clouds, the existence of ubiquitous substellar, cold H 2 globules in planetary nebulae and supernova remnants, or the mere existence of comets suggest that the physics of very cold interstellar gas might be much richer than usually envisioned. At the extreme of low temperatures ( < ∼ 10 K), H 2 itself is subject to a phase transition crossing the entire cosmic gas density scale. Aims. This well-known, laboratory-based fact motivates us to study the ide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Consequently the fluid temperature rises only slightly on compression, and the pressure response is therefore smaller than for condensate-free gas. 1 1 Füglistaler and Pfenniger (2015) suggested that the adiabatic sound-speed of H 2 in phase equilibrium is zero, corresponding to infinite adiabatic compressibility. Their result was obtained by scaling the isothermal sound speed, which is zero in phase equilibrium, by the ratio of specific heats, C P /C V , which they assumed to be finite.…”
Section: Equations Of Statementioning
confidence: 99%
See 1 more Smart Citation
“…Consequently the fluid temperature rises only slightly on compression, and the pressure response is therefore smaller than for condensate-free gas. 1 1 Füglistaler and Pfenniger (2015) suggested that the adiabatic sound-speed of H 2 in phase equilibrium is zero, corresponding to infinite adiabatic compressibility. Their result was obtained by scaling the isothermal sound speed, which is zero in phase equilibrium, by the ratio of specific heats, C P /C V , which they assumed to be finite.…”
Section: Equations Of Statementioning
confidence: 99%
“…However, at constant pressure the fluid releases/absorbs heat without any change in temperature, in response to condensation/sublimation of the solid. Consequently C P is infinite, whereas C V is not, so the method of sound-speed calculation suggested by Füglistaler and Pfenniger (2015) does not yield a well-defined result.…”
Section: Equations Of Statementioning
confidence: 99%
“…The nongravitational acceleration has been postulated to be driven by radiation pressure (Micheli et al 2018), which could be explained if 'Oumuamua was an ultralow-density fractal aggregate (Moro-Martín 2019b; Sekanina 2019; Luu et al 2020) or a millimeter-thin artificial light sail (Bialy & Loeb 2018). If the nongravitational acceleration was powered by cometary outgassing (Micheli et al 2018;Seligman et al 2019), it has been demonstrated that the energetics are consistent with the sublimation of H 2 (Füglistaler & Pfenniger 2015;Seligman & Laughlin 2020;, N 2 , or CO (Seligman et al 2021). Recently, Flekkøy & Brodin (2022) calculated infrared and optical spectral signatures that would differentiate between the various proposed scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The non-gravitational acceleration has been postulated to be driven by radiation pressure (Micheli et al 2018), which could be explained if 'Oumuamua was an ultra low-density fractal aggregate (Moro-Martín 2019; Luu et al 2020;Sekanina 2019), or a millimeter-thin artificial light sail (Bialy & Loeb 2018). If the non-gravitational acceleration was powered by cometary outgassing (Micheli et al 2018;Seligman et al 2019), it has been demonstrated that the energetics are consistent with the sublimation of H 2 (Füglistaler & Pfenniger 2015;Seligman & Laughlin 2020;, N 2 , or CO (Seligman et al 2021).…”
Section: Introductionmentioning
confidence: 99%